2017
DOI: 10.1002/jsfa.8680
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ influxes and transmembrane transport are essential for phytic acid degradation in mung bean sprouts

Abstract: CaCl enhanced Ca influxes and accumulation in cells, which contributed to the regulation of phytic acid degradation. This study demonstrates that calcium channels play an essential role in mediating phytic acid degradation in mung bean sprouts, and both extracellular and intracellular Ca -regulation were involved in phytic acid degradation. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…). It is well known that La 3+ inhibits influx of extracellular Ca 2+ into cells across plasma membrane by competing with Ca 2+ due to their radii . Maruyama et al identified 2‐APB as an IP 3 receptor inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…). It is well known that La 3+ inhibits influx of extracellular Ca 2+ into cells across plasma membrane by competing with Ca 2+ due to their radii . Maruyama et al identified 2‐APB as an IP 3 receptor inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that La 3+ inhibits influx of extracellular Ca 2+ into cells across plasma membrane by competing with Ca 2+ due to their radii. 17 Maruyama et al 25 identified 2-APB as an IP 3 receptor inhibitor. Bootman et al 26 and Braun et al 27 found that it was an inhibitor of store-operated Ca 2+ channels (SOC) and transient receptor potential (TRP) channels because it could affect intracellular Ca 2+ signals with complex mechanisms and multiple acting targets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations